2013
DOI: 10.1177/1359105313510336
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pluralistic ignorance on the provision of health care for people who inject drugs

Abstract: Health workers who work with people who inject drugs may believe that their colleagues hold less favorable attitudes toward health services for people who inject drugs than themselves-a phenomenon termed pluralistic ignorance. This research explores whether the presumed attitudes of their colleagues, rather than their own attitudes, predict the behavioral intentions of health workers toward people who inject drugs. A total of 57 hospital-based health workers were surveyed to assess their attitudes toward harm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(58 reference statements)
0
9
1
Order By: Relevance
“…People with drug or alcohol use disorders-more than 20 million Americans 2 -are far too often judged, mistreated, and untreated by the very people who aim to help them and who, by regarding SUD not as a chronic illness but as a moral weakness, justify withholding care. 6 Stigma Against People With SUD Addiction is a medical disorder characterized by profound alterations in brain circuitry subjected to repeated substance exposure. 7 More common in people with genetic, environmental, or developmental risk factors, these alterations affect reward processing, which is necessary to motivate and prioritize behaviors; executive function, which is necessary for self-regulation; and mood, which is necessary for well-being.…”
mentioning
confidence: 99%
“…People with drug or alcohol use disorders-more than 20 million Americans 2 -are far too often judged, mistreated, and untreated by the very people who aim to help them and who, by regarding SUD not as a chronic illness but as a moral weakness, justify withholding care. 6 Stigma Against People With SUD Addiction is a medical disorder characterized by profound alterations in brain circuitry subjected to repeated substance exposure. 7 More common in people with genetic, environmental, or developmental risk factors, these alterations affect reward processing, which is necessary to motivate and prioritize behaviors; executive function, which is necessary for self-regulation; and mood, which is necessary for well-being.…”
mentioning
confidence: 99%
“…In the meantime, pluralistic ignorance is a social phenomenon regarding the most common misperception that occurs when a person has an individual view of him/herself and mistakenly assumes that the overwhelming majority of the group holds the opposite view [19]. Pluralistic ignorance is widely applied to a variety of psychological and social environments concerning risk behaviour, including social projection [20], community values [23], virtual community [26], and drug users [27]. In light of the many research studies on pluralistic ignorance, which have focused on the adaptation of problematic social norms, this study found that pluralistic ignorance in some cases can give rise to the adoption of positive and productive norms in terms of employees' pro-environmental behaviour in the collective spirit of Chinese society.…”
Section: Discussionmentioning
confidence: 99%
“…Brener et al [27] The study explored whether the hypothetical attitudes of colleagues, rather than their own, predicted health workers' behavioural intentions towards others who inject drugs.…”
Section: De Larios Andmentioning
confidence: 99%
“…When researchers use proportional and/or comparative questioning to measure pluralistic ignorance, they might rely on the other-score as the primary predictor (e.g., Halbesleben, 2009). When researchers use discrete questioning, they might also rely on the other-score (e.g., Flezzani & Benshoff, 2003), or they might rely on other- and self-scores as simultaneous predictors or controls, where appropriate (e.g., Brener et al, 2015). Sometimes, other scores are directly reported by participants, whereas other times they are experimentally manipulated (e.g., Geiger & Swim, 2016).…”
Section: Variation In Using Pluralistic Ignorance-related Individual-level Scores As Predictorsmentioning
confidence: 99%